Hubungan Perilaku Seksual Remaja SMU Dengan Status Pernikahan Orang Tua di Kota Mataram Nusa Tenggara Barat - Mukminah Mukminah; Djauhar Ismail; Abdul Wahab (Biota, 2016)
The condition of family life whereby there is divorce or separation will either mentally or psychologically affect children in the family that becomes more obvious as the children grow up. Moreover, when there are other factors that support the behavior. To identify association between sexual behavior of senior high school teenagers and marital status of parents at Mataram Municipality Nusa. Data analysis used chi square (χ²) and logistic regression at confidence interval 95%. Result: Marital status of parents was significantly associated with sexual behavior of teenagers with p-value 0.0001 and PR 2.03 (CI 95% 1.65-2.50). The result of bivariate analysis showed significant association between variable of peers’ influence with p value 0.0001 and PR 2.40 (CI95% 1.90-3.04) and variable of mass media exposure with p-value 0.0001 and PR 3.92 (CI 95% 2.42-6.36) and sexual behavior of teenagers. The result of logistic regression analysis showed marital status of divorced parents had the probability of increasing sexual behavior of teenagers as much as 19% after being controlled by variables of peers’ influence and mass media exposure. Conclusion: Marital status of parents was associated with sexual behavior of teenagers. Teenagers whose parents were divorced had the probability for higher sexual behavior than those whose parents were not divorced.